Kualitas Fisik dan Kimia Sungai Citarum yang bermuara ke Waduk Cirata di Wilayah Kabupaten Cianjur - Bramantiyo Eko Putro; Isma Masrofah (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
Pollution prevention must be carried out in the upstream, middle and downstream parts. One of the Citarum watersheds located in the middle part is the Cirata reservoir. Pollution in the Cirata reservoir does not only originate from the reservoir environment, but also from rivers that flow into the Cirata reservoir. Cirata Reservoir besides being a Hydroelectric Power Plant (PLTA) unit, this reservoir is also used by the community for fish farming in the Floating Net Pool (KJA) technique. This study aims to determine the most dominant pollutants contaminating the Cirata reservoir. Test of river and reservoir water quality is carried out with the help of lab tests by Labkesda. The research data was obtained by obtaining clean water quality test data from several 3 estuary points of the river flow to the Cirata reservoir and 4 centers of Cirata reservoir number of 40 samples. Data processing techniques are carried out using data mining, namely Exploratory Data Analysis. The lab parameter test results, which are compared with the Permenkes No. 32 Year 2017 standard, show that the majority of the physical and chemical quality parameters of the Citarum River which empties into the Cirata Reservoir are still within the required threshold. Most river and reservoir water samples have water quality that qualifies as clean water. Five samples (12.5%) in turbidity parameters and 1 sample (2.5%) in color samples did not qualify as clean water. This is possible because the sampling is too close to the mainland. Temperature parameters of 20 samples (50%) do not qualify as clean water is possible because of the lag time of sampling. The results of the analysis showed that the distance of pollutant sources, the amount of pollutant sources, and environmental conditions around the sampling significantly with temperature, TDS, turbidity, color, pH, nitrogen, iron, hardness, manganese, fluoride, and cyanide.